THE MEDIATION ROLE OF JOB SATISFACTION ON PERCEIVED ORGANIZATIONAL SUPPORT TOWARDS ORGANIZATIONAL COMMITMENT OF MALINI ULUWATU RESTAURANT EMPLOYEES - Kadek Citra Naraswari; I Gusti Ayu Dewi Adnyani; I Gusti Made Suwandana (Adisam Publisher, 2026)
The objective of this research is to investigate and clarify how organizational commitment is influenced by perceived organizational support, utilizing job satisfaction to mediate this relationship. Through a quantitative methodology, this research intends to offer a deeper understanding of the mechanisms by which favorable organizational perceptions boost commitment via enhanced worker satisfaction. The empirical observation targeted 98 staff members of the Malini Uluwatu Seafood & Sunset Restaurant, employing a census or saturated sampling technique within a non-probability sampling framework. Data collection was carried out through interviews and questionnaires. The analysis technique used is Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach. The results of the analysis show that 1) perceived organizational support has a positive and significant effect on employee organizational commitment, 2) perceived organizational support has a positive and significant effect on employee job satisfaction, 3) job satisfaction has a positive and significant effect on employee organizational commitment, 4) job satisfaction mediates the effect of perceived organizational support on employee organizational commitment in a complementary partial. The implications of this study theoretically support the findings of previous studies through the perspective of Social Exchange Theory. The practical implications of this study provide policy references for organizational leaders and management to increase employee organizational commitment through perceived organizational support and job satisfaction.